Gender equality in the professional workplace : pioneering radical action for women's empowerment - Vollum-Dix, Karen (Women, economy and labour relations ;, 2025)
Despite a century of progress since the realisation of women's suffrage in the US and UK, gender inequalities persist in politics, in the workplace, and within organisations. The persistent lack of women in influential positions, shaped by structural bias, harassment, and discrimination, underscores the hurdles that women still encounter. Despite progress, significant barriers remain, casting a shadow over women in the professional spheres. In Gender Equality in the Professional Workplace, author Karen R. Vollum-Dix delves into the ongoing gender equality struggle by examining women's challenges in powerful roles. She addresses issues like workplace harassment, institutional misogyny, and executive role disparities. Vollum-Dix aims to inspire impactful actions for lasting change. Introducing the new concept of Auto-duoethnography and incorporating Ecofeminism, Radical Feminism, and Futures and Foresight, the study explores the author's experiences, challenges, and the potential future scenarios concerning women's social and professional positions. While the central focus is on women's roles, her work also acknowledges how societal shifts, like recent challenges to recruitment procedures, affect men, thereby prompting a broader consideration of both genders. Ultimately, Vollum-Dix's work underscores the need for everyone to learn and unlearn in response to changing workplaces and societies. Professionals across various fields, including gender studies, human resources, diversity and inclusion, organisational leadership, social sciences, and women's advocacy, benefit from Vollum-Dix's insight. Additionally, individuals in positions of authority, managers, policymakers, and those concerned with addressing gender disparities and advancing women's empowerment in workplaces and society discover insightful viewpoints in this important work.